2008
DOI: 10.1021/ef8007294
|View full text |Cite
|
Sign up to set email alerts
|

Some Biogenic-Related Compounds Occluded inside Asphaltene Aggregates

Abstract: The occluded compounds inside asphaltene aggregates were released from 16 asphaltenes through mild degradation processes oxidized by the H2O2/CH3COOH system. Prior to the oxidation procedure, all of the n-C7 asphaltenes (n-heptane-insoluble asphaltenes) were subjected to Soxhlet extraction by acetone continuously for 240 h to rule out interferences from the adsorbed/co-precipitated compounds, which were likely introduced during the asphaltene preparation processes. Among these occluded compounds, a series of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 47 publications
2
20
0
Order By: Relevance
“…Sixteen asphaltenes from the Tarim Basin, NW China, were analyzed for trapped hydrocarbons (Yang et al, 2009), among which the series of even carbon numbered n-alk-1-enes have been recovered from 13 samples, which generally ranged from C 16 eC 30 with the ratios of the paired -ene/-ane >1. Besides these alkenes, in the trapped fraction 22,29,30-trisnorhop-17(21)-ene and 17a-hop-20(21)-ene were detected from 3 asphaltenes, and C 23 tricyclic terp-12(13)-ene and C 29 18a-30-norneohop-13(18)-ene were found in another 3 asphaltenes (Yang et al, 2009).…”
Section: Asphaltenesmentioning
confidence: 99%
See 1 more Smart Citation
“…Sixteen asphaltenes from the Tarim Basin, NW China, were analyzed for trapped hydrocarbons (Yang et al, 2009), among which the series of even carbon numbered n-alk-1-enes have been recovered from 13 samples, which generally ranged from C 16 eC 30 with the ratios of the paired -ene/-ane >1. Besides these alkenes, in the trapped fraction 22,29,30-trisnorhop-17(21)-ene and 17a-hop-20(21)-ene were detected from 3 asphaltenes, and C 23 tricyclic terp-12(13)-ene and C 29 18a-30-norneohop-13(18)-ene were found in another 3 asphaltenes (Yang et al, 2009).…”
Section: Asphaltenesmentioning
confidence: 99%
“…However, recent studies have shown that a series of even carbon numbered n-alk-1-enes are present in the trapped fractions of asphaltenes (Yang et al, 2009;Zhao et al, 2010Zhao et al, , 2012Tian et al, 2012) and solid bitumens (Cheng et al, 2012(Cheng et al, , 2013. They may be stable in these geomacromolecules owing to the protection afforded by the matrix, which inhibits transformation of the trapped n-alk-1-enes during later geochemical processes.…”
Section: Introductionmentioning
confidence: 99%
“…Well protected from secondary alteration events, these occluded hydrocarbons represent the original oil derived from kerogen (Liao et al, 2006). A H 2 O 2 /CH 3 COOH oxidative system was used to release occluded hydrocarbons from the asphaltenes (Liao et al, 2005(Liao et al, , 2006Yang et al, 2009;Zhao et al, 2010). The procedure, details of which can be found in Liao et al (2006), included the preparation of asphaltenes by n-hexane precipitation, acetone extraction of n-hexane-asphaltenes to obtain the adsorbed fraction, and H 2 O 2 /CH 3 COOH oxidation of the acetone-extracted asphaltenes to release the occluded fraction.…”
Section: Release Of the Hydrocarbons Adsorbed/occluded Inside Asphaltmentioning
confidence: 99%
“…The adsorbed fractions also gave evidence of biodegraded oil mixed with normal oils, with no obvious odd to even predominance, but enrichment with high carbon number hydrocarbons (C 30 +). However, the occluded fraction inside the corresponding asphaltenes shows different distribution characteristics, without evidence of biodegradation, but slight even carbon number predominance and the presence of even carbon number terminal n-alkenes (Liao et al, 2006;Yang et al, 2009;Zhao et al, 2010). Liao et al (2005Liao et al ( , 2006 proposed that these hydrocarbons, including n-alkenes, were retained in the skeleton of asphaltenes during the early stage from kerogen to oil.…”
Section: Overall Characteristics Of the Marine Oil Reservoirs In The mentioning
confidence: 99%
“…n-C 20 D 42 released by H 2 O 2 / CH 3 COOH treatment belonged to the occluded compounds inside the macromolecular structures of asphaltenes according to the previous reports. 1,16,17,26 Detection of n-C 20 D 42 in the oxidized products of the acetone-extracted pyrolysates (Figure 8) suggests that the targeted compound indeed occluded inside asphaltenes during the experiments.…”
Section: Energy and Fuelsmentioning
confidence: 99%